Effect of Nickel Addition into Sn-3Ag-0.5Cu on Intermetallic Compound Formation during Soldering on Copper - Siti Rabiatull Aisha, Idris; Ali, Ourdjini; Y.T., Chin (2012)
Doping lead-free solders with minor additions of alloying and impurity elements such as Ni, Bi or Zn appears to have major effects on the growth of intermetallics (IMC) in solder joints during reflow soldering between the Sn-AgCu lead-free solders and the surface finish metallurgy. In this paper, the results of the effect of small Nickel additions (0.05 and 0.1 wt%) on intermetallic formation during soldering with Sn-3Ag-0.5Cu (SAC305) are presented. The Ø500µm solder alloys of Sn-3Ag-0.5Cu, Sn-3Ag-0.5Cu0.05Ni and Sn-3Ag-0.5Cu-0.1Ni were investigated in detail after reflow soldering at 250oC on copper finish and isothermally aged at 150oC for up to 2000 hours. The results show that after reflow soldering, scallop-type Cu6Sn5/ (Cu, Ni)6Sn5 was the only reaction product formed. A strong influence of Ni addition on the growth rate and thickness of the Cu3Sn layer was also observed. Addition of as little as 0.05wt% Ni to SAC305 solder effectively slows down the growth of this Cu3Sn phase while growth of the Cu6Sn5 continued to increase with increasing in aging time.